2022
DOI: 10.3390/microorganisms10071410
|View full text |Cite
|
Sign up to set email alerts
|

Resistome Analysis of Campylobacter jejuni Strains Isolated from Human Stool and Primary Sterile Samples in Croatia

Abstract: Campylobacteriosis represents a global health challenge due to continuously increasing trends of antimicrobial resistance in Campylobacter jejuni. C. jejuni can sometimes cause life-threatening and severe systematic infections (bacteremia, meningitis, and other extraintestinal infections) with very few antibiotics left as treatment options. Bearing in mind that C. jejuni is the predominant species in humans, in this paper, we present a study of the C. jejuni differences in antimicrobial resistance and genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…( Iovine, 2013 ). The determinants of drug resistance do not always confer resistance phenotypes, and single resistance determinant may correlate weakly with certain antibiotics ( Šoprek et al, 2022 ). In this study, we found that the overall correlation between the 16 antibiotic resistance determinants detected with ResFinder v.4.1 and phenotypic resistance was not strong, and that there were huge differences between the different antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…( Iovine, 2013 ). The determinants of drug resistance do not always confer resistance phenotypes, and single resistance determinant may correlate weakly with certain antibiotics ( Šoprek et al, 2022 ). In this study, we found that the overall correlation between the 16 antibiotic resistance determinants detected with ResFinder v.4.1 and phenotypic resistance was not strong, and that there were huge differences between the different antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the strains were selected from the collection of C. jejuni at the Croatian Veterinary Institute, collected within other studies on Campylobacter spp. during a period of 2021–2022 [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The human strains were collected in the University Hospital for Infectious Diseases (samples ZG01, ZG02, ZG03, ZG06, ZG07, ZGI07, ZG12) and included strains from stool and blood samples of patients with diarrhea also during 2021 and 2022. These isolates were previously analyzed for the antimicrobial resistance [ 10 ] and added to other ST-21 isolates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation